2008
DOI: 10.1002/rra.1056
|View full text |Cite
|
Sign up to set email alerts
|

Optimum fish passage and guidance designs are based in the hydrogeomorphology of natural rivers

Abstract: Understanding hydrodynamic cues used by outmigrating juvenile salmon (emigrants) to guide fine-scale swim path selection is critical to successful fish guidance and passage at man-made structures. We show how these cues can be inferred from channel features and complex flow fields of natural rivers through which emigrants pass. We then describe a new cue, 'total hydraulic strain', integrating properties of flow acceleration and turbulence through the spatial gradients in velocity to create a single flow field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 41 publications
(29 reference statements)
0
53
0
Order By: Relevance
“…Recently, the first example of combining genomic studies with field telemetry of Pacific salmon identified the factors that are associated with migration failure in freshwater [143]. Integration of fish telemetry with detailed hydrodynamic studies has been used to optimize fish passage facilities through improved understanding of fish cognition and behaviour [144]. The number of such integrative studies appears to be increasing.…”
Section: Combining Electronic Tagging With Other Research Methodsmentioning
confidence: 99%
“…Recently, the first example of combining genomic studies with field telemetry of Pacific salmon identified the factors that are associated with migration failure in freshwater [143]. Integration of fish telemetry with detailed hydrodynamic studies has been used to optimize fish passage facilities through improved understanding of fish cognition and behaviour [144]. The number of such integrative studies appears to be increasing.…”
Section: Combining Electronic Tagging With Other Research Methodsmentioning
confidence: 99%
“…A number of studies have reported Pacific salmon smolts performing milling behaviours in anthropogenically altered channels (Venditti et al 2000;Plumb et al 2006;Nestler et al 2008). The present study showed that milling behaviours also occur in Atlantic salmon smolts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study is among the first to quantify the behaviour of downstream migrating smolts using high resolution telemetry (Ehrenberg and Steig 2003;Goodwin et al 2006;Nestler et al 2008), particularly in shallow rivers. The results showed that Atlantic salmon smolts performing milling behaviours covered a larger area (m 2 ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care should be taken to ensure that velocity and depth requirements are met continuously along likely fish movement paths. Multiple field studies indicate that fish exploit boundary layers created by objects in the flow field (Fausch, 1993;Nestler et al, 2008). Interstitial spaces within the center of the chute may provide zones of lower velocity for smaller fish.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%